Analisis Kepuasan Pengguna terhadap Layanan Streaming Video dengan Metode E-service quality: Studi Kasus pada Aplikasi Disney Plus - Sabrina Jovanka; Ade Maulana (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
The advancement of information technology has transformed the landscape of the entertainment and media industry with the emergence of various streaming services such as Disney Plus. In this context, user satisfaction becomes a key factor in retaining and attracting new users to both platforms. Recognizing the importance of assessing user satisfaction, the aim of this study is to evaluate the level of user satisfaction using the Disney Plus service and identify elements that need improvement to enhance user satisfaction with the application. This research method employs a descriptive statistical approach to compare the level of user satisfaction, particularly in the E-service quality variable. The results indicate that overall, the level of user satisfaction with Disney Plus is quite good. The study also highlights Responsiveness as one of the aspects that needs improvement in the Disney Plus application. With an overall mean variable value of 4.16, Disney Plus is categorized as a satisfying application, indicating that users are satisfied with the services provided by the platform. In conclusion, user satisfaction evaluation is an important aspect of digital service development, and with a good understanding of user preferences and needs, platforms like Disney Plus can continue to improve the quality of their services to retain and attract more users.